2014
DOI: 10.1182/blood-2014-03-560441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies reveal an unexpected negative regulatory role for Jak2 in thrombopoiesis

Abstract: • Jak2 deletion in PLTs andMKs leads to thrombocytosis due to dysregulated TPO turnover.• Jak2 loss in PLTs/MKs induces non-autonomous expansion of stem/progenitors, and specifically of MK-primed hematopoietic stem cells (HSCs).JAK inhibitor treatment is limited by the variable development of anemia and thrombocytopenia thought to be due to on-target JAK2 inhibition. We evaluated the impact of Jak2 deletion in platelets (PLTs) and megakaryocytes (MKs) on blood counts, stem/ progenitor cells, and Jak-Stat signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…42 Additionally, adrenergic stresses were found to induce a more apparent increase in the platelet counts in mice with the c-Mpl homozygous mutation, probably because TPO/c-Mpl does not work on terminal MK maturation and even negatively regulate platelet shedding through Janus kinase-signal transducer and activator of transcription signaling activation. [43][44][45] This finding also suggests that the sympathetic stimulation may play an important role in maintaining thrombopoiesis when the TPO/c-Mpl-associated pathway is defective.…”
Section: Discussionmentioning
confidence: 48%
“…42 Additionally, adrenergic stresses were found to induce a more apparent increase in the platelet counts in mice with the c-Mpl homozygous mutation, probably because TPO/c-Mpl does not work on terminal MK maturation and even negatively regulate platelet shedding through Janus kinase-signal transducer and activator of transcription signaling activation. [43][44][45] This finding also suggests that the sympathetic stimulation may play an important role in maintaining thrombopoiesis when the TPO/c-Mpl-associated pathway is defective.…”
Section: Discussionmentioning
confidence: 48%
“…42 This has been well demonstrated in 3 murine models. [43][44][45] Here, we clearly demonstrate that the thrombocytosis induced by MPLS204P is not due to a defect in cell trafficking of the receptor. In contrast, MPLS204P is a weak gain-of-function mutant in signaling, inducing constitutive STAT activation using sensitive approaches and an increased and more prolonged ligand-induced STAT phosphorylation than MPLWT.…”
mentioning
confidence: 68%
“…[50][51][52] Recent studies confirmed the specificity of the Pf4-Cre model to mature MKs and platelets using Mpl and JAK2 deletion or JAK2-V617F expression. 24,[53][54][55] Accordingly, Dnm2 fl/fl Pf4-Cre mice had normal erythrocyte counts and volumes, and granulocyte and monocyte counts were increased only by 30%, whereas these parameters are severely altered in JAK2-V617F knockin mouse models. [56][57][58][59][60] DNM2 deletion in HSPCs is expected to severely alter erythropoiesis, because ubiquitous Dnm2 deletion is lethal in mice before embryonic day 8.5, 8 a stage in which first erythrocytes circulate and the heterozygous DNM2 loss-of-function mutation V235G induced by chemical mutagenesis is associated with iron deficiency anemia due to impaired transferrin uptake in mice.…”
Section: Discussionmentioning
confidence: 99%